OP11 Ileocecal resection for recently diagnosed ileocecal Crohn's disease is associated with improved long-term outcomes compared to anti-tumor necrosis factor therapy: a population-based study. (30th January 2023) - Agrawal, M; Ebert, A; Poulsen, G; Ungaro, R; Faye, A; Jess, T; Colombel, J F; Allin, K
Abstract: Background: Early treatment of Crohn's disease (CD) often involves biologics such as anti-tumor necrosis factor (anti-TNF) agents. Ileocecal resection (ICR), while a therapeutic option in early CD, is generally reserved for complicated CD or when medical treatment fails. We aimed to compare long-term outcomes of ICR and anti-TNF therapy as index treatment for ileocecal CD, initiated within one year of diagnosis, in the Danish nationwide cohort. Methods: Using cross-linked nationwide registers, we identified all individuals who lived in Denmark and were diagnosed with ileal CD between 2003 and 2018. We included individuals who underwent ICR or received anti-TNF drugs as index treatment for ileocecal CD within one year of diagnosis. We excluded patients who did not have pathology information confirming disease in the ileocecal region. The primary outcome was a composite of CD-related hospitalization, systemic corticosteroid exposure, CD-related surgery, and perianal CD diagnosis. We conducted Cox proportional hazards regression analyses to compare outcomes in the two groups after adjusting for potential confounders. We also determined the proportion of individuals initiated on immunomodulator (IMM), anti-TNF, or no therapy at 5 years after ICR. Results: Of the 16, 443 individuals diagnosed with ileocecal CD between 2003 and 2018, 581 (3.5%) and 698 (4.2%) individuals with confirmed disease in the ileocecal region underwent ICR and received anti-TNF as the index treatment, respectively. The composite outcome occurred in 273 individuals (IR 110.3/100, 0 person years (PY)) in the ICR group and in 318 individuals (IR 201.9/100, 0 PY) in the anti-TNF group. The risk of the composite outcome was 33% lower in the ICR group compared to the anti-TNF group (aHR 0.67; 95% CI 0.54, 0.83), after adjusting for demographic and clinical variables. On analysis of individual outcomes, ICR was associated with reduced risk of systemic corticosteroid exposure and CD-related surgery, but not CD-related hospitalization or perianal CD diagnosis. Of individuals who underwent ICR, the proportion that was initiated on IMM, anti-TNF treatment or no treatment at 5 years of follow up was 47.5%, 17.1%, and 50.3%, respectively. Conclusion: These data support the role of ICR as an index treatment for ileocecal CD and challenge the current paradigm of reserving surgery for complicated CD refractory or intolerant to medications. Further studies will help identify characteristics of individuals who needed no treatment after ICR.